2007
DOI: 10.1039/b708433c
|View full text |Cite
|
Sign up to set email alerts
|

Pre-association of polynuclear platinum anticancer agents on a protein, human serum albumin. Implications for drug design

Abstract: The interactions of polynuclear platinum complexes with human serum albumin were studied. The compounds examined were the "non-covalent" analogs of the trinuclear BBR3464 as well as the dinuclear spermidine-bridged compounds differing in only the presence or absence of a central -NH(2)-(+) (BBR3571 and analogs). Thus, closely-related compounds could be compared. Evidence for pre-association, presumably through electrostatic and hydrogen-bonding, was obtained from fluorescence and circular dichroism spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 29 publications
(43 reference statements)
0
40
0
1
Order By: Relevance
“…5 Cytotoxicity and cellular accumulation have also been shown to be charge-dependent. 1,7 1,0,1/ t,t,t has undergone Phase I 8 and Phase II 9,10 clinical trials, the only Pt( II ) agent structurally distinct from cisplatin and its analogs to do so. The products of degradation in blood plasma can be replicated by reactions with sulfur-containing proteins such as glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…5 Cytotoxicity and cellular accumulation have also been shown to be charge-dependent. 1,7 1,0,1/ t,t,t has undergone Phase I 8 and Phase II 9,10 clinical trials, the only Pt( II ) agent structurally distinct from cisplatin and its analogs to do so. The products of degradation in blood plasma can be replicated by reactions with sulfur-containing proteins such as glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…[161] nESI-QToF-MS and HPLC-ICP-MS experiments concluded that oxaliplatin was forming adducts with transferrin as the intact parent molecule as well as its hydrolysed species, in a stoichiometry that was concentration-dependent, but with no information of the potential binding sites on the protein. [162] The trinuclear platinum complex BBR3464 has also been characterised for its interactions with purified HSA using multiple techniques including ESI-MS. [163] Thanks to the central platinum moiety, a pre- Ruthenium-based complexes have also been studied for their interaction with serum proteins using different MS techniques. Once more, the results described in the literature concerning the selectivity and the affinity of ruthenium-based metallodrugs with serum proteins are quite controversial.…”
Section: Interactions Of Metallodrugs With Serum and Serum Proteinsmentioning
confidence: 99%
“…We describe the crosslinked nanoparticles, and also procedures for testing the degree of nanoparticle stability. Finally, for protein-based nanoparticles, it is essential to ensure that the protein molecules retain their native configuration, in order to preserve their specific functions [for HSA, this is the binding and transport of small molecules (Fehske et al 1981;Frokjaer and Otzen 2005;Goldwasser and Feldman 1997;Gonzalez and Kannewurf 1998;Griffel and Kaufman 1992;Kragh-Hansen 1981;Montero et al 2007;Peters 1985;Putnam 1984;Rainey and Read 1994)], and to avoid the potentially dangerous effects of denaturation, such as triggering amyloid formation (Schnabel 2010;Goldschmidt et al 2010;Balbirnie et al 2001;Nelson et al 2005). …”
Section: Introductionmentioning
confidence: 99%